PENGARUH PENDEKATAN STEAM TERHADAP HIGHER ORDER THINKING SKILL (HOTS) DI SEKOLAH DASAR - Nofia Henita; Desyandri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to determine the impact of the STEAM approach on higher order thingking skills in elementary schools. This research is a quasy experiment design. The design form of this study is Nonequivalent Control class Design. The results showed that the STEAM approach applied in the experimental class was very effective against higher order thingking skills. The hypothesis test results with a sig value of 0.001 lower than the significance level of 0.05 then a decision can be made that H0 is rejected and H1 is accepted where there is a significant difference between the higher order thingking skill control class and the experimental class